OXIDATIVE STRESS AND SERUM FERRITIN STATUS IN RHEUMATOID ARTHRITIS PATIENTS - 2Sapkota S1, Shakya L (Journal of Biomedical and Pharmaceutical Research, 2017)
Aim : The study was aimed to study the serum ferritin level as a response to oxidative stress in Rheumatoid arthritis patients and to measure the degree of oxidative stress in them by estimating the level of vitamin C. Methods: The study included 50 patients who were clinically diagnosed as patients with RA and 50 age and sex matched healthy volunteers. Blood samples were collected from them and serum ferritin and serum vitamin C were estimated. Results: The level of Vitamin C was found to be significantly decreased in the patients than in the healthy controls. Whereas, serum ferritin level showed significant rise in the patients as compared to the healthy controls. Conclusions: The significant rise in serum ferritin is highly associated with higher oxidative stress in rheumatoid arthritis patients as compared to the normal healthy controls. Serum ferritin acts as an acute phase reactant and its rise is due to inflammatory response to the rising oxidative stress in rheumatoid arthritis. Keywords: Ferritin, Oxidative stress, Rheumatoid arthritis, Vitamin C